Engineered tubular structures based on chitosan for tissue engineering applications. (February 2018) - Silva, Joana M; Rodrigues, Luísa C; Silva, Simone S; Reis, Rui L; Duarte, Ana Rita C
The development of versatile tubular structures is a subject of broad interest in tissue engineering applications. Herein, we demonstrate the production of tubular structures based on chitosan through a combination of dipping, freeze-drying and supercritical technology approaches. The combination of these techniques yields versatile tubes with a perfectly defined hollow imprint, which upon chemical cross-linking with genipin acquire enhanced mechanical properties (Young Modulus ( E ) and ultimate tensile stress (σmax )), as well as improved stability in wet conditions. The biological performance reveals that cells remain attached, well-spread and viable on the surface of cross-linked tubes. As so, is envisioned that our methodology opens up new avenues on tissue engineering approaches, where the design of tubular structures with tuned length, diameter and elasticity is required.